Social media use among adolescents with eating disorders: a double-edged sword - Nawaz, Faisal A.; Riaz, Mehr Muhammad Adeel; Banday, Nimrat ul ain; Singh, Aakanksha; Arshad, Zara; Derby, Hanan; Sultan, Meshal A. (Frontiers in Psychiatry, 2024)
Eating disorders are on the rise with a significant impact on mental health. Misuse of social media platforms is likely a significant contributing factor. This trend is especially pronounced among adolescents, who are increasingly using social media platforms for communications, building relationships, learning and entertainment. The unsupervised sharing of social media content can have drastic consequences on the physical and psychological wellbeing of youth, which often takes the form of "thinspiration" or "fitspiration". This probably serves as a trigger for those already struggling with eating disorders. In addition, there is a lack of awareness among youth and adults on ideal knowledge-sharing practices related to an eating disorder. By addressing the unique challenges that social media presents for youth with eating disorders, communities can work towards creating a safer and more supportive online environment on a global scale. At this junction, this article aims to share the current challenges of social media use among adolescents with eating disorders and put forth recommendations for how social media could be used as a tool for positive impact in this population.